PENDEKATAN ARSITEKTUR PERILAKU PADA PERANCANGAN RUMAH SUSUN DI KAWASAN KUMUH BELAWAN - Ahsan, Dwi Adrean; Utami, Wahyu (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
According to RI Law Number 20 of 2011 Flats are buildings or buildings built in an environment, both horizontally and vertically, each unit of which can be used and owned separately, one of which is in the form of a residence and also equipped with parts that can be used together. Vertical housing such as flats is still a solution to overcome crowded and slum care environments. The design of flats in the Belawan slum area using a behavioral architectural approach aims to create a comfortable and safe residential space in a slum environment. Therefore, the behavioral architectural approach is used as a design method that focuses on understanding human behavior in utilizing residential space. It is hoped that these flats can provide a comfortable and safe living environment for residents of the Belawan slum area, as well as significantly improve their quality of life.